Synthesis and characterization of mixed ligand metal(II) complexes with Schiff base and 8-hydroxyquinoline as ligands - Abubakar Abdullahi Ahmed; Joy Peter; Fatima Ngaramu (Journal of Chemistry Letters)
Co(II), Ni(II) and Cu(II) mixed ligand complexes have been synthesized from a Schiff base (L) obtained by the condensation reaction of acetophenone and 2-aminophenol, as primary ligand and 8-hydroxyquinoline (HQ) as secondary ligand. The Schiff base and metal(II) mixed ligand complexes were accordingly investigated using some physicochemical techniques. The Schiff base ligand was shiny brown crystalline solid obtained in low yield of 36.21 % with melting point of 240 oC. The metal(II) complexes were obtained as brown to deep brown coloured solids, air stable with decomposition temperature of 310 – 340 oC. The molar conductivity values of the complexes in dimethylformamide (DMF) was found to be 2.13 - 3.77 Ohm-1cm2mol-1 indicating their non-electrolytic nature. The determination of water of crystallization showed presence of 1½ uncoordinated water molecules in the Co(II) and Cu(II) complexes while 2 was estimated for Ni(II) complex. The infrared spectral data allude that, on complexation, the Schiff base ligand loses its phenolic hydrogen and coordinated bidentately to the metal(II) ions through deprotonated phenolic oxygen and imine nitrogen (HC=N-) as monobasic ligand. Similarly, HQ coordinated via deprotonated phenolic oxygen and quinoline nitrogen. The resultant data showed that the mixed ligand might be formulated as [ML(HQ)].nH2O exhibiting four-coordinate square planar geometry.